Perception of the flash flood hazard by the population of Mindelo, S.Vicente (Cape Verde) - Martins, Bruno Manuel dos Santos de Castro (2018)
[Review status: This preprint has been withdrawn by the authors] São Vicente Island (Republic of Cape Verde) lies within the Sahelian zone and faces several natural hazards, one of which is the flash flooding hazard. Based on a questionnaire entitled Flash Flood Hazard Perception in Cape Verde applied to 199 subjects, we seek to specifically ascertain some of the factors which influence behavioural decision making to 10 be adopted by populations when confronted with this natural hazard. In order to identify the primary factors associated with the perception of flash flood risk, it was conducted a multivariate technique of the main components analyses (PCA). The results obtained on this study suggest that women present higher levels of knowledge on this type of natural hazard. The study reveals minor statistical differences between the groups with and without prior experience of flash floods concerning perceptions, causal attributions, knowledge and perception of support from public entities regarding flash flood hazard. 15 There is a significant association between causal attributions and the degree of knowledge regarding flash floods hazard, suggesting that the individuals who tend to attribute the phenomenon of flash floods to external factors, evidence adequate knowledge on this type of natural hazard.